(untitled) (International Journal of Environmental Sciences, 2025)
Software development for a medical device has to take into account what motivates the product’s value by examining the market (i.e., the end user) while factoring in the feasibility, regulatory, and safety nuances involved with its use. In contrast to most consumer-software firms, which can beta test new applications with a large, diverse group of end users. In the initial phase of the software development life cycle, officially the idea or concept phase, clinical professionals will examine the customer (the doctor) and the marketplace. Next, in collaboration with clinical partners, cardiac professionals will create proposals for possible new product concepts or reasons for redesigns that would be advantageous to the physician customers and, ultimately, the patients being treated. From there, proposals are commented upon by software engineers based on feasibility, time, cost, and other related requirements that could pose development issues. The design & development phase is where most of the design work takes place and gets documented, and where most of the costs of developing a new product are incurred. The next step is to draft the software requirements specification (SRS) and user requirements specification (URS) after the terms of product development have been agreed upon. The SRS describes the specific features and anticipated performance of the program, while the URS identifies the physician’s needs, which is somewhat self-evident.